Preparation and Study on the Single-Crystal Structure of Flurbiprofen–Salicylamide Co-crystal - Hou, Jia-Wei; Gong, Yan-Qing; Li, Gang; Ma, Li-Wen; Pan, Hong-Juan; Shan, Han-Bin; Zhong, Jia-Liang (Pharmaceutical Fronts, 2023)
Co-crystals can improve the physicochemical properties of pharmaceutical active ingredients, and thus have great potential in improving drug performance. Some studies have obtained the powder spectrum of the co-crystal of flurbiprofen (FBP) and salicylamide (2-OHBZA) but have not obtained a single-crystal structure. In this study, co-crystals of FBP-2-OHBZA with a molar ratio of 1:1 were obtained by slow evaporation using ethyl acetate and tetrahydrofuran for verification. Density functional theory was used to optimize the structure of the hydrogen bond and π−π stacking formed by the co-crystal of FBP and 2-OHBZA. The assay results of the co-crystals of FBP-2-OHBZA are in good agreement with the calculated values reported.
Keywords: flurbiprofen; salicylamide; co-crystals; density functional theory